FRI0170 Effect of alcohol on response to therapy with TNF-a inhibitors for rheumatoid arthritis: Results from corrona registry. (23rd January 2014) - Pala, O.; Messing, S.; Hopkins, A.; Reed, G.; Perez-Rivera, M.; Acosta, M.; Kremer, J.M.; Lozada, C.; Pappas, D.A.
Abstract : Background: TNF-α inhibitors (TNFi) have revolutionized the therapy of Rheumatoid Arthritis (RA). However, up to 30% of patients (pts) fail to respond to treatment (tx) with TNFi or respond inadequately. While moderate alcohol (ETOH) consumption exerts an anti-inflammatory effect in RA, little is known about ETOH influence on response to tx with TNFi. Objectives: To evaluate the effect of ETOH on response to TNFi tx using data from the large US cohort of pts participating in the Consortium of Rheumatology Researchers of North America (CORRONA). Methods: The CORRONA registry is a network of over 100 private and academic rheumatology practices across the U.S with 30, 537 RA pts. Mean duration of follow up (fu) per patient is 3.4 years (SD: 2.6). Pts have been followed for up to 10.2 years. Cumulative length of fu for all RA pts is 61, 918 years. We identified biologic naive patients at the time of TNFi initiation and followed them for 6 months. We investigated the association of different levels of ETOH consumption with response to TNFi tx at 6 months. Outcomes of interest included DAS28, CDAI, mHAQ levels and EULAR response after 6 months on TNFi. Regression models to isolate the effect of ETOH on outcomes included baseline values of the outcome of interest, age, gender, race, concurrent DMARD tx. Results: 2, 764 naïve TNFi initiators with at least 6 months of fu and ETOH consumption data were identified from registry inception until 12/2010. ETOH consumption was categorized at the time of TNFi initiation as "Not at all"(1650, 60%); "Occasional" (515, 19%); "1-3 beverages/week"(472, 17%); ">3 beverages/week" (127, 4%). The last group was slightly older, included more males with slightly longer RA duration. The first group was more likely to be on concurrent tx with methotrexate and on a higher dose of prednisone. All other baseline demographic and disease characteristics were similar including seropositivity. Disease activity and functionality measures at baseline were statistically higher for pts not consuming or occasionally consuming ETOH compared to the other two groups (Table). Regression modeling results comparing each of the groups did not reveal a significant effect of level of ETOH consumption with response to TNFi. The only exception was the comparison at 6 months' CDAI between the ">3 beverages/week" pts vs "not at all" which showed a more favorable effect of higher ETOH consumption on 6 month CDAI values (beta 2.8, 95%CI 1.4-4.2, p: <0.05). Only the level of baseline CDAI was persistently associated with CDAI after 6 months on TNFi across our regression models – and this was independent of level of ETOH consumption. Conclusions: Data from a very large number of US pts in the CORRONA registry do not support a differential effect of ETOH consumption on response to TNFi, although a cross sectional analysis suggests a possible overall effect on disease. Disclosure of Interest: O. Pala: None Declared, S. Messing: None Declared, A. Hopkins Employee of: University of Miami Miller School of Medicine, G. Reed Grant/Research support from: CORRONA, Consultant for: CORRONA, Employee of: University of Massachusetts Medical School, Paid Instructor for: Harvard Medical School, M. Perez-Rivera Employee of: University of Miami Miller School of Medicine, M. Acosta Employee of: University of Miami Miller School of Medicine, J. Kremer Shareholder of: CORRONA, Grant/Research support from: Abbott, Amgen, AstraZeneca, BMS, Genentech, Lilly, Pfizer, Consultant for: Amgen, Genentech, Lilly, Pfizer, Employee of: CORRONA, Speakers Bureau: Abbott, Amgen, BMS, Pfizer, C. Lozada: None Declared, D. Pappas: None Declared